Article-level metrics and what they tell us about the impact of PLOS publications - Pattinson, Damian (Septentrio Conference Series, 2014)
PLOS launched its Article-Level Metrics (ALMs) programme in 2009 as an alternative to the crude journal-level metrics that scientists have relied upon for so long to identify important research. ALMs allow readers to see how many views, downloads, citations and shares an individual paper has received, and thus to determine its impact on a field. Over the past year, the ALMs programme has been expanded to include social media information, such as Facebook likes and Tweets, and novel web tools such as Mendeley and Citeulike. Researchers are now using this information to examine the links between early activity indicators and long-term citation data, and to identify what tools best predict truly impactful research. In this session I will present the latest additions to PLOS's ALMs suite, and show some data on what these metrics tell us about the impact of papers published in PLOS journals.